A revisiting of early 18th-century environmental data to identify Gulf of Lion properties before the industrial era - M. Locritani; S. Garvani; S. Garvani; G. Tamburello; A. Guarnieri; A. Guarnieri; G. Manzella (Earth System Science Data, 2025)
The work Histoire physique de la mer, authored by Luigi Ferdinando Marsili (or Marsigli) and published in 1725, is one of the earliest texts detailing observations of the physical, biological, and bathymetric characteristics of the sea, mainly concentrating on the Gulf of Lion in southern France's Mediterranean area. Nonetheless, understanding Marsili's findings is difficult due to the application of non-standard measurement units and the imprecision of georeferencing data. The MACMAP project (A Multidisciplinary Analysis of Climate Change Indicators in the Mediterranean and Polar Regions), which is funded by the Istituto Nazionale di Geofisica e Vulcanologia, has involved a thorough recalibration of Marsili's observations. This project focused on transforming water weight measurements obtained from different locations in the Gulf of Lion from June 1806 to January 1807 into water density values. The sampling sites were digitised, bathymetric profiles were reconstructed, and tide amplitudes were examined. The main objective is to make these historical data available to compare with current measurements. The data are available under the following DOIs: http://oceano.bo.ingv.it/erddap/search/index.html?page=1&itemsPerPage=1000&searchFor=marsili (Locritani et al., 2024b), https://doi.org/10.13127/histoiremarsili/sealevel (Locritani et al., 2024a), and https://doi.org/10.13127/histoiremarsili/waterdensity (Locritani and Garvani, 2024).